High-performance magnesium-rare earth alloy material for aero-engine and preparation method and application thereof
By using a multi-element magnesium alloy system based on Nd and Gd and precise heat treatment processes, the problems of insufficient fatigue resistance and plasticity of yttrium-free magnesium alloy materials have been solved, resulting in a magnesium alloy material with high strength and excellent fatigue resistance, suitable for aerospace equipment.
Patent Information
- Application Number
- CN202611286592.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-11-06
AI Technical Summary
Existing yttrium-free magnesium alloys are insufficient in terms of fatigue resistance, plasticity, and high strength, making it difficult to meet the stringent service requirements of the aerospace field.
Using Nd and Gd as the main strengthening elements, supplemented by Ag, Zr and Zn, a multi-element magnesium alloy system is formed. By precisely controlling the content of each element and the heat treatment process, including solution treatment and aging treatment, an ideal aged structure with fine and dispersed precipitates and discontinuous grain boundaries is formed.
It achieves high strength, excellent plasticity and superior fatigue resistance of magnesium alloy materials, meeting the usage requirements of harsh service scenarios such as aerospace.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This application relates to the field of magnesium alloy materials technology, and in particular to a high-performance magnesium rare earth alloy material for aero-engines, its preparation method and application. Background Technology
[0002] Currently, magnesium alloys commonly used in aerospace castings can be divided into four main systems: high-strength heat-resistant magnesium alloys represented by WE43A, high-strength magnesium alloys represented by EV31A, ultra-high-strength magnesium alloys represented by VW93, and rare-earth-free magnesium alloys represented by AZ91. However, all four types of alloys have limitations in application: WE43A and VW93 both contain yttrium, which is easily oxidized during smelting to form yttrium oxide inclusions that are difficult to remove. These inclusions can easily enter the casting during pouring, causing early failure. VW93 can only be used in scenarios where fatigue performance is not required. Although EV31A does not contain yttrium, its yield strength is lower than that of WE43A, making it unsuitable for the load-bearing requirements of heavy-duty transmission housings. AZ91 has relatively low performance and cost, and is mainly used in the automotive field, making it unsuitable for aerospace applications. In addition, the ZM2, ZM5, and ZM6 magnesium alloys commonly used in domestic aerospace castings also suffer from insufficient strength, making them unsuitable for high-load service scenarios. Therefore, developing high-performance magnesium alloys with yield strength comparable to WE43A, yttrium-free, and excellent casting properties is an urgent need in the aerospace application field.
[0003] To fill the performance gap in yttrium-free magnesium alloys, numerous explorations have been undertaken in existing technologies. For example, Chinese patent application CN122061055A discloses a yttrium-free rare-earth magnesium alloy, which achieves improved strength and fatigue resistance in a yttrium-free system by adjusting the addition of rare-earth elements such as Nd and Gd, and by synergistically optimizing the smelting process and heat treatment parameters. However, the overall service performance of this alloy still has significant limitations: at a stress level of 100±50 MPa, its fatigue cycle count is approximately 7.7 million cycles, and its fatigue resistance remains at a low level, making it difficult to support the requirements of long-life aerospace components; at the same time, its plasticity is only 4%~6%, and its deformation coordination ability is insufficient, further limiting its application under complex stress conditions.
[0004] In summary, there is an urgent need to develop a yttrium-free cast magnesium alloy material that combines excellent fatigue resistance, good plasticity, and high strength to meet the stringent service requirements of the aerospace field. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of existing yttrium-free magnesium alloys that cannot simultaneously possess excellent fatigue resistance, plasticity and high strength, and to provide a method for preparing magnesium alloy materials.
[0006] Another object of the present invention is to provide a magnesium alloy material prepared by the above preparation method.
[0007] Another objective of this invention is to provide the application of the above-mentioned magnesium alloy material in the manufacture of aerospace equipment.
[0008] Another object of the present invention is to provide a magnesium alloy part.
[0009] The above-mentioned objective of this invention is achieved through the following technical solution: This invention protects a method for preparing a magnesium alloy material, comprising the following steps: S1. After melting preheated Mg-Nd master alloy, Mg-Zr master alloy, Mg-Gd master alloy, pure Zn, pure Ag and pure Mg, RJ5 refining agent is added for compound refining. After casting and cooling, the casting is obtained. S2. The casting obtained in step S1 is subjected to solution treatment, quenched in air, and then the quenched casting is subjected to aging treatment and cooled to obtain the magnesium alloy material. In step S2, the conditions for the solution treatment are as follows: the casting is first kept at 360~380 ℃ for 3~4 h, and then heated to 520~530 ℃ and kept at 520~530 ℃ for 8~10 h; The aging treatment conditions are: 200~220 ℃, 16~20 h; Both steps S1 and S2 are performed under a protective gas atmosphere; The magnesium alloy material comprises the following components by weight percentage: Nd 1.8%~2.5%, Gd 3.4%~4.0%, Zn 0%~0.2%, Ag 0.2%~0.5%, Zr 0.1%~0.3%, with the remainder being magnesium.
[0010] To overcome the problem that existing yttrium-free magnesium alloys cannot simultaneously possess excellent fatigue resistance, plasticity, and high strength, this invention designs a multi-element magnesium alloy system with Nd and Gd as the main strengthening elements, supplemented by Ag, Zr, and Zn for synergistic regulation. By precisely controlling the content of each element and matching it with the heat treatment process, a synergistic improvement in plasticity, strength, and fatigue resistance is achieved.
[0011] During the solid solution strengthening stage, this invention controls the weight percentage of Nd to be 1.8%~2.5% and Gd to be 3.4%~4.0%. Solid solution treatment allows both to fully dissolve into the magnesium matrix to form a supersaturated solid solution. Gd exhibits higher solid solution strengthening efficiency than Nd, directly improving the matrix yield strength. Simultaneously, the total solid solution content of Gd+Nd is strictly limited to avoid excessive solute causing excessive lattice distortion, thereby suppressing slip localization and preventing solute atoms from oversaturating and agglomerating at grain boundaries to form a continuous network precipitate. This prevents grain boundaries from being fragmented and weakened, thus maintaining the matrix's plastic deformation capacity while ensuring resistance to fatigue crack initiation. After solid solution treatment, air quenching is employed to obtain a highly supersaturated non-equilibrium solid solution, laying the microstructure foundation for subsequent aging precipitation.
[0012] Regarding aging precipitation and grain refinement, subsequent aging treatment promotes the precipitation of Mg5Gd phase from Gd and Mg phase from Nd. 12 The Nd phase, along with two types of nanoscale precipitates, is dispersed within the grains. Through the Orovan mechanism, it effectively hinders dislocation movement, significantly improving yield strength and delaying fatigue crack initiation. Simultaneously, the precipitates at grain boundaries pin the grain boundaries, inhibiting grain growth, and synergistically strengthen the grains with the Zr-refined fine grains. This results in a more uniform distribution of cyclic slip and a more tortuous crack propagation path, thereby simultaneously improving fatigue resistance. Furthermore, when the Zr content is controlled at 0.1%–0.3%, it not only refines the grains but also maintains the continuity of the matrix structure, further enhancing the alloy's plasticity.
[0013] Meanwhile, Ag, within the range of 0.2% to 0.5%, promotes the uniform nucleation of aged precipitates, effectively avoiding the coarse equilibrium phases and continuous network precipitation at grain boundaries caused by local over-aging or under-aging. This eliminates the potential for stress concentration at the interface between soft and hard regions, reduces the tendency for strain localization during deformation, and while suppressing early crack initiation under alternating loads, also improves the uniform deformation capacity of the matrix, which is beneficial for maintaining and enhancing plasticity. Zn, limited to 0% to 0.2%, can form long-period stacked ordered phases (LPSO phases) within this range to enhance alloy plasticity. At the same time, it avoids excessive consumption of rare earth elements and reduces the number of effective β' strengthening phases. Thus, while ensuring yield strength, it maintains sufficient precipitation strengthening contribution and avoids the deterioration of fatigue resistance due to insufficient strengthening phases, ultimately achieving synergistic optimization of plasticity gain, strength, and fatigue resistance.
[0014] In summary, by precisely matching the content of the specific elements mentioned above with the process parameters of "solution treatment + quenching + aging", this invention successfully enables the magnesium alloy to simultaneously achieve high strength, excellent plasticity and superior fatigue resistance, which can meet the usage requirements of harsh service scenarios such as aerospace.
[0015] In this invention, magnesium is the main component, and its weight percentage in the magnesium alloy material is ≥90%.
[0016] Furthermore, in step S1, the preheating temperature is 200~300 ℃.
[0017] Furthermore, in step S1, the preheating time is 1.5 to 3 hours.
[0018] Furthermore, in step S1, the protective gas atmosphere includes one or more of SF6, CO2, and Ar.
[0019] Furthermore, in step S1, the protective gas atmosphere is SF6 and CO2.
[0020] Preferably, the volume ratio of SF6 to CO2 is 1:(25~35).
[0021] Furthermore, in step S1, the preheating of the container is included before melting.
[0022] Furthermore, the container preheating step involves heating the molten container at 690~730 ℃ for 1~1.5 h.
[0023] Further, in step S1, the smelting specifically includes the following steps: First, the Mg-Gd master alloy, Mg-Nd master alloy, pure Zn, pure Ag and pure Mg are heated and melted. Then, the temperature is increased and the Mg-Zr master alloy is added. The mixture is melted and homogenized to obtain a melt.
[0024] Furthermore, the melting temperature is 690~730 ℃.
[0025] Furthermore, the temperature for the heating is 790~810 ℃.
[0026] Furthermore, the mixing time is 5 to 10 minutes.
[0027] Furthermore, in step S1, the gas atmosphere for the composite refining is argon.
[0028] Furthermore, in step S1, the temperature of the composite refining is 730~750 ℃.
[0029] Furthermore, in step S1, the time for the compound refining is 5 to 20 minutes.
[0030] Furthermore, in step S1, the compound refining also includes a settling step.
[0031] Furthermore, the settling time is 25-35 minutes.
[0032] Furthermore, in step S1, the pouring temperature is 750~760 ℃.
[0033] Furthermore, in step S1, the pouring time is 30~180 s.
[0034] Furthermore, in step S2, the protective gas atmosphere is CO2.
[0035] Furthermore, as a preferred method, the specific operation of the CO2 protective atmosphere is as follows: First, dry the container in a CO2 atmosphere at a temperature of 110~140 ℃ for 1~1.5 h. After drying, place the casting obtained in step S1 into a heat treatment furnace, evacuate to -40 kPa, and then fill with CO2 to 0 kPa. Repeat this cycle three times to form a CO2 protective atmosphere.
[0036] Preferably, the container is a vacuum thermal reactor.
[0037] Furthermore, the magnesium alloy material comprises the following components by weight percentage: Nd 2.0%~2.5%, Gd 3.5%~4.0%, Zn 0%~0.2%, Ag 0.3%~0.5%, Zr 0.1%~0.3%, with the remainder being magnesium.
[0038] In this invention, the weight percentages of Nd, Gd, Zn, Ag, Zr, and Mg were determined in accordance with GB / T 13748.20-2024.
[0039] This invention protects the magnesium alloy material prepared by the above-described preparation method.
[0040] This invention protects the application of the above-mentioned magnesium alloy material in the manufacture of aerospace equipment.
[0041] This invention protects a magnesium alloy component made from the aforementioned magnesium alloy material.
[0042] Compared with the prior art, the present invention has the following beneficial effects: This invention provides a method for preparing a magnesium alloy material, comprising the following components by weight percentage: Nd 1.8%~2.5%, Gd 3.4%~4.0%, Zn 0%~0.2%, Ag 0.2%~0.5%, Zr 0.1%~0.3%, with the remainder being magnesium. The magnesium alloy material is obtained through specific solutions treatment, air quenching, and aging treatment. This invention, through precise matching of specific element contents and the "solution + quenching + aging" process parameters, ensures an ideal aged microstructure with fine, dispersed precipitates within the grains and discontinuous grain boundary distribution. Ultimately, this enables the alloy to simultaneously achieve high strength, excellent plasticity, and superior fatigue resistance, meeting the application requirements of demanding service scenarios such as aerospace. Detailed Implementation
[0043] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in this technical field.
[0044] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.
[0045] RJ5 refining agent: produced by Liaoning Yangchen Hongyu Metallurgical Materials Co., Ltd.
[0046] Example 1: A magnesium alloy material and its preparation method 1. Magnesium alloy materials By weight percentage, it includes the following components: Nd 2.0%, Gd 3.5%, Zn 0.2%, Ag 0.3%, Zr 0.3%, with the remainder being magnesium.
[0047] 2. Preparation methods of magnesium alloy materials S1. Prepare the raw materials by weight percentage by preheating the Mg-Nd master alloy, Mg-Zr master alloy, Mg-Gd master alloy, pure Zn, pure Ag and pure Mg at a temperature of 260 ℃ for 2.5 h to obtain the pretreated raw materials. S2. Under a protective gas atmosphere of 3%SF6 and 97%CO2, the crucible and melting tools are heated at 720 °C for 1.2 h until the crucible turns dark red. Then, the Mg-Gd master alloy, Mg-Nd master alloy, pure Zn, pure Ag and pure Mg from the pretreated raw materials obtained in step S1 are put into the preheated crucible and mixed. The mixture is heated to 690 °C to melt, and then heated to 800 °C. The Mg-Zr master alloy is added to melt it. The mixture is stirred and mixed for 10 min to obtain the melt. S3. Mix the melt obtained in step S2, RJ5 refining agent and argon gas, and perform compound refining at 740 ℃ for 15 min. After refining, let it stand for 30 min without removing the bottom slag to obtain the refined melt. S4. Pour the refined melt obtained in step S3 into the mold at a pouring temperature of 750 ℃ and a pouring time of 60 s. After cooling and solidification, remove the mold to obtain the casting. S5. Before solution treatment, the vacuum heat treatment furnace is dried in a CO2 atmosphere at a temperature of 120 ℃ for 1 hour. After drying, the casting obtained in step S4 is placed in the vacuum heat treatment furnace, and a vacuum is drawn to -40 kPa. Then, CO2 is introduced to 0 kPa, and this cycle is repeated three times to form a CO2 protective atmosphere. Solution treatment is then performed in this atmosphere: the casting is held at 370 ℃ for 3 hours, then heated to 525 ℃ and held for 9 hours. After solution treatment, the resulting solution-treated casting is quenched in air, and then aged at 210 ℃ for 18 hours. After cooling, the magnesium alloy material is obtained.
[0048] Example 2: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Nd is adjusted from 2.0% to 2.5%.
[0049] The other steps and conditions are the same as in Example 1.
[0050] Example 3: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Gd is adjusted from 3.5% to 4.0%.
[0051] The other steps and conditions are the same as in Example 1.
[0052] Example 4: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Zn is adjusted from 0.2% to 0%.
[0053] The other steps and conditions are the same as in Example 1.
[0054] Example 5: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Ag is adjusted from 0.3% to 0.5%.
[0055] The other steps and conditions are the same as in Example 1.
[0056] Example 6: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Zr is adjusted from 0.3% to 0.1%.
[0057] The other steps and conditions are the same as in Example 1.
[0058] Comparative Example 1: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Nd is adjusted from 2.0% to 2.8%.
[0059] The other steps and conditions are the same as in Example 1.
[0060] Comparative Example 2: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Gd is adjusted from 3.5% to 5.0%.
[0061] The other steps and conditions are the same as in Example 1.
[0062] Comparative Example 3: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Zn is adjusted from 0.2% to 0.4%.
[0063] The other steps and conditions are the same as in Example 1.
[0064] Comparative Example 4: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Ag is adjusted from 0.3% to 0.7%.
[0065] The other steps and conditions are the same as in Example 1.
[0066] Comparative Example 5: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Ag is adjusted from 0.3% to 0%, that is, no Ag is added.
[0067] The other steps and conditions are the same as in Example 1.
[0068] Comparative Example 6: A magnesium alloy material and its preparation method The difference from Example 1 is that the weight percentage of Zr is adjusted from 0.3% to 0.7%.
[0069] The other steps and conditions are the same as in Example 1.
[0070] Comparative Example 7: A magnesium alloy material and its preparation method A magnesium alloy material was prepared by following the steps of Example 1 in CN122061055A. It exhibits a tensile strength of 315 MPa, a yield strength of 202 MPa, and an elongation of 6%, achieving a good balance between high strength and high ductility. This makes it the yttrium-free magnesium alloy system with the best overall performance in this patent.
[0071] Comparative Example 8: A magnesium alloy material and its preparation method The difference from Example 1 is that in step S5, the heat preservation at 370 ℃ for 3 h is adjusted to heat preservation at 370 ℃ for 1.5 h.
[0072] The other steps and conditions are the same as in Example 1.
[0073] Comparative Example 9: A magnesium alloy material and its preparation method The difference from Example 1 is that in step S5, the aging process time is adjusted from 18 h to 14 h.
[0074] The other steps and conditions are the same as in Example 1.
[0075] Comparative Example 10: A magnesium alloy material and its preparation method The difference from Example 1 is that in step S5, the quenching is changed from air quenching to water quenching at 60 °C.
[0076] The other steps and conditions are the same as in Example 1.
[0077] Experimental Example 1: Performance Testing of Magnesium Alloy Materials 1. Experimental Methods Yield strength and plasticity: Tested according to GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Test at room temperature"; Fatigue resistance: Axial constant amplitude high-cycle fatigue tests were conducted on specimens with a width of 20 mm and a thickness of 5 mm according to GB / T 3075-2008 "Method for Controlling Axial Force in Fatigue Testing of Metallic Materials". The loading frequency was 30 Hz and the stress ratio R=0.33. Cycle life was tested under two stress levels: maximum stress of 150 MPa and minimum stress of 50 MPa (i.e., 100±50 MPa) and maximum stress of 180 MPa and minimum stress of 60 MPa (i.e., 120±60 MPa). Based on these results, SN curves were plotted and the fatigue limit was determined.
[0078] 2. Experimental Results Table 1 Performance data for each embodiment and comparative example
[0079] Note: " / " in the table indicates that the test was not performed.
[0080] As shown in Table 1, the magnesium alloy materials in Examples 1-6 all possess the synergistic advantage of high strength and good plasticity: yield strength ≥185 MPa and plasticity ≥5%. Regarding fatigue performance, at a stress level of 100±50 MPa, the cycle life consistently exceeds 1×10⁻⁶. 7 It exhibits excellent fatigue resistance; even at higher stress levels of 120±60 MPa, the cycle life remains at least 2.8×10⁻⁶. 6The magnesium alloy rare earth material exhibits excellent fatigue resistance after more than one cycle. These results demonstrate that the magnesium alloy rare earth material prepared by this invention possesses excellent fatigue resistance, good plasticity, and high strength.
[0081] In contrast, in Comparative Example 1, due to the excessively high weight percentage of Nd, the excess solute exacerbated lattice distortion and induced local slip. The age-supersaturated Nd could not precipitate entirely as a fine β' phase within the grains, instead coarsening extensively along grain boundaries to form a continuous network of Mg. 12 The Nd phase severely disrupts grain boundaries and weakens bonding forces, leading to a brittle matrix and reduced plasticity and fatigue resistance. Similarly, in Comparative Example 2, due to the excessively high weight percentage of Gd, excessive Gd accumulates at grain boundaries and precipitates coarse Mg5Gd phases, damaging grain boundary strength and causing deterioration in plasticity and fatigue resistance.
[0082] In Comparative Example 3, due to the excessive weight percentage of Zn, the excess Zn preferentially combines with Gd / Nd, consuming the rare earth solute intended to form the β' strengthening phase. This results in a significant reduction in the effective β' phase volume fraction, and the yield strength and fatigue resistance deteriorate due to insufficient precipitation strengthening.
[0083] In Comparative Example 4, due to the excessively high weight percentage of Ag, the excess Ag no longer acts as a uniform nucleation promoter. Instead, it reacts with Gd and Nd to form coarse Ag-RE-rich intermetallic compounds, further reducing the effective concentration of solid-solid rare earth elements in the matrix. As a result, the age-hardening gain decreases after reaching saturation, leading to a deterioration in both plasticity and fatigue resistance. In Comparative Example 5, the absence of Ag resulted in a lack of uniform nucleation sites provided by Ag. During the aging process, the nucleation sites for the precipitated phases were scarce and uneven. Some areas rapidly coarsened due to over-aging, while other areas were under-aged and insufficiently strengthened. This led to the appearance of discontinuous coarse equilibrium phases and localized network precipitation at grain boundaries. At the same time, stress concentration at the soft and hard interfaces became an early crack initiation source, resulting in a deterioration in fatigue resistance.
[0084] In Comparative Example 6, due to the excessive weight percentage of Zr, the Zr exceeding the solid solution limit could not dissolve into the matrix and remained in the microstructure as undissolved zirconium particles, forming hard and brittle inclusions. This disrupted the continuity of the matrix microstructure and became stress concentration points and preferred crack nucleation sites under alternating loads, resulting in poor plasticity and fatigue resistance.
[0085] Comparative Example 7 not only lacks the kinetic conditions for uniform nucleation, but also the deviation in the intrinsic composition of the matrix changes the driving force for the precipitation of the equilibrium phase. Even under ideal nucleation conditions, the expected β' phase-dominated structure cannot be obtained. Instead, it tends to form coarse equilibrium phases and continuous network precipitation at grain boundaries. At the same time, the risk of stress concentration at the soft and hard interfaces is aggravated, resulting in poor fatigue resistance.
[0086] In Comparative Example 8, due to the short holding time of the solution treatment, elements such as Nd and Gd did not fully dissolve into the magnesium matrix, resulting in insufficient supersaturated solid solubility. Subsequent aging lacked sufficient solute supply, leading to a small number of precipitated phases and consequently, poor plasticity and fatigue resistance. In Comparative Example 9, due to the short holding time of the aging treatment, strengthening phases such as β' did not have time to disperse and precipitate within the grains, and the microstructure remained in an under-aged state, resulting in weak precipitation strengthening effect and consequently, poor yield strength and fatigue resistance. In Comparative Example 10, due to improper quenching conditions, large residual stress or local micro-strain concentration was generated inside the microstructure, leading to early crack initiation under alternating loads and consequently, poor fatigue resistance.
[0087] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for producing a magnesium alloy material, characterized by, Includes the following steps: S1. After melting preheated Mg-Nd master alloy, Mg-Zr master alloy, Mg-Gd master alloy, pure Zn, pure Ag and pure Mg, RJ5 refining agent is added for compound refining. After casting and cooling, the casting is obtained. S2. The casting obtained in step S1 is subjected to solution treatment, quenched in air, and then the quenched casting is subjected to aging treatment and cooled to obtain the magnesium alloy material. In step S2, the conditions for the solution treatment are as follows: the casting is first kept at 360~380 ℃ for 3~4 h, and then heated to 520~530 ℃ and kept at 520~530 ℃ for 8~10 h; The aging treatment conditions are: 200~220 ℃, 16~20 h; Both steps S1 and S2 are performed under a protective gas atmosphere; The magnesium alloy material comprises the following components by weight percentage: Nd 1.8%~2.5%, Gd 3.4%~4.0%, Zn 0%~0.2%, Ag 0.2%~0.5%, Zr 0.1%~0.3%, with the remainder being magnesium.
2. The preparation method according to claim 1, characterized in that, The magnesium alloy material comprises the following components by weight percentage: Nd 2.0%~2.5%, Gd 3.5%~4.0%, Zn 0%~0.2%, Ag 0.3%~0.5%, Zr 0.1%~0.3%, with the remainder being magnesium.
3. The preparation method according to claim 1, characterized in that, In step S1, the temperature of the composite refining is 735~750 ℃.
4. The preparation method according to claim 1, characterized in that, In step S1, the smelting specifically includes the following steps: First, the Mg-Gd master alloy, Mg-Nd master alloy, pure Zn, pure Ag and pure Mg are mixed and heated to melt. Then, the temperature is increased and the Mg-Zr master alloy is added. The mixture is melted and homogenized to obtain a melt.
5. The preparation method according to claim 4, characterized in that, The melting temperature is 690~730 ℃.
6. The preparation method according to claim 4, characterized in that, The temperature for the heating is 790~810 ℃.
7. The preparation method according to claim 1, characterized in that, In step S1, the pouring temperature is 750~760℃.
8. The magnesium alloy material prepared by the preparation method according to any one of claims 1 to 7.
9. The application of the magnesium alloy material of claim 8 in the manufacture of aerospace equipment.
10. A magnesium alloy component, characterized in that, It is made from the magnesium alloy material described in claim 8.
Citation Information
Patent Citations
High-strength magnesium-rare earth alloy material for force-bearing casing of aviation transmission system and preparation method of high-strength magnesium-rare earth alloy material
CN122061055A
